Revisiting the Effectiveness of Transcranial Direct Current Brain Stimulation for Cognition: Evidence, Challenges, and Open Questions - Marian E. Berryhill (Frontiers Research Topics, 2017)
The aim of this Frontiers Research Topic is to assemble a collection of papers from experts in the field of non-invasive brain stimulation that will discuss (1) the strength of the evidence regarding the potential of tDCS to modulate different aspects of cognition; (2) methodological caveats associated with the technique that may account for the variability in the reported findings; and (3) a set of challenges and future directions for the use of tDCS that can determine its potential as a reliable method for cognitive rehabilitation, maintenance, or enhancement.